2005
DOI: 10.1590/s1020-49892005000500008
|View full text |Cite
|
Sign up to set email alerts
|

Falls among elderly persons in Latin America and the Caribbean and among elderly Mexican-Americans

Abstract: The prevalence of falls had a large variation among the countries studied. Some of the risk factors that we identified could be modified so as to help prevent falls in older people in these populations. The factors deserving attention include depressive symptoms, functional limitations, diabetes, and urinary incontinence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
61
3
35

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(107 citation statements)
references
References 38 publications
8
61
3
35
Order By: Relevance
“…1 Outro estudo realizado por Reyes-Ortiz et al (2005) mostra que a prevalência de quedas tem uma grande variação de acordo com os países investigados. 12 Os dados do presente estudo foram mais elevados em relação ao estudo citado acima, que mostrou variação de prevalência . Em países orientais a freqüência de quedas é menor, aproximadamente 15% dos idosos caem uma vez ao ano.…”
Section: Discussionunclassified
“…1 Outro estudo realizado por Reyes-Ortiz et al (2005) mostra que a prevalência de quedas tem uma grande variação de acordo com os países investigados. 12 Os dados do presente estudo foram mais elevados em relação ao estudo citado acima, que mostrou variação de prevalência . Em países orientais a freqüência de quedas é menor, aproximadamente 15% dos idosos caem uma vez ao ano.…”
Section: Discussionunclassified
“…In Beijing, China, Yu et al 2 found a prevalence of falls of 18% associated with age from 60 to 70 years, female sex, low level of physical activity, poor eyesight, living alone, and other health problems, such as diabetes. In Latin American countries, Reyes-Ortiz et al 3 found prevalences of 27% in Uruguay, 28.5% in Argentina, and close to 34% in Santiago, Chile, and Mexico City. In Brazil, Mota et al 4 studied an elderly population in the Rio de Janeiro municipal area, finding prevalence of falls of 30.3% associated with female sex, advanced age, divorce, living alone, poor ARTIGO ARTICLE health conditions, low functional capacity, and little life satisfaction.…”
Section: Introductionmentioning
confidence: 97%
“…Studies by researchers in different regions of the world currently report different prevalences for the outcome "falls among the elderly" 2,3,4,5,6 . In Beijing, China, Yu et al 2 found a prevalence of falls of 18% associated with age from 60 to 70 years, female sex, low level of physical activity, poor eyesight, living alone, and other health problems, such as diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…Ninety per cent of these accidents could have been prevented if there have been adult supervision [4].Home accidents are also a big problem between the elderly, researches indicate that a third of people aged 65 and older fall down each year, being half of them not just one but multiple falls. A lot of these falls are related with hospitalization, institutionalization, hip fractures, fear of falling, mortality and other consequences [5].…”
Section: Related Workmentioning
confidence: 99%